Definition and important features of concessions in European Union law - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Abstract: The subject of the legal analysis in this work is the definition and important features of concessions in EU law. Special attention was paid to the transfer of the operational risk, which appears as the key feature of that definition. Consideration is based on relevant EU Regulations and to a more significant extent on the practice of the EU Court of Justice, which is inevitable in this area. At the same time, the analysis points to open issues and flaws regarding normative state of play in the given area. The work contains a conclusion that the EU Directive on Concessions on 2013, for the first time, in a more comprehensive manner, tries to define the concession and establish its important features. In that autonomous concept of the concessions, it actually raises the transfer of the operational risk to a level of the most important concession feature in EU law. Nevertheless, even beside the significant attention paid to this matter, its norm frames keep containing open issues and flaws. It is particularly visible in reference to inaccuracy and non-alignment of legal solutions. The EU Court of Justice will have the leading role in making these flaws right. However, one should not omit also certain possibilities of the respective Members States’ national laws in that regard.
Keywords: Key words: concession, important features, EU law, Directive on Concessions, operational risk, the EU Court of Justice